Travestis e (re)ações à violência sofrida nos espaços de prostituição na cidade de Campina Grande – PB - Braz, Ednaldo da Costa (2016)
The dissertation aimed to problematize the transvestite’s discourses on Reactions to violence pervaded by the transvestites and prostitution in the city of Campina Grande - PB. To achieve this goal, a mapping of the prostitution spaces used by transvestites in the city of Campina Grande was carried out, a contextualization of the conditions under which they experience the prostitution, as well as the understanding of the meanings of transvestite, prostitution and violence in their speeches, in order to identify the strategies and tactics used by transvestites prostitutes in face of the violence experienced on the streets. Therefore, different methodological strategies were used such as the field visit, field diary, participant observation and semi-structured interviews. The results obtained from the reports confirm that the destabilization due to its gender performance makes transvestites the favorite victims of transphobic violence. As a way to react to violence, the strategy most used by transvestites is to walk together, to be in a group, having as a purpose the fear of their aggressors, because "beating a transvestite when being alone it is easier for the transphobic, but if they are together it would be a way of imposition against them". The travestites researched respond in different ways to the violence to be able to experience their performances of feminine gender, in order survive exercising the prostitution activity.